20,000 leagues under the sea - Disney, Walt, 1901-1966.; Felton, Earl.; Fleischer, Richard; Douglas, Kirk, 1916-2020; Mason, James, 1909-1984.; Lukas, Paul, 1894-1971.; Lorre, Peter; Wilke, Robert J., 1914-1989; De Corsia, Ted.; Kerrigan, J. M. (Joseph M.), 1884-1964.; Verne, Jules, 1828-1905.; Walt Disney Pictures; et al. ([United States] : Walt Disney Home Entertainment ; Burbank, Calif. : Buena Vista Home Entertainment, 2003)
A trouble-shooting 19th century seaman is trying to discover why so many whaling ships have been disappearing. Teaming with a scientist and a diver, they set sail to investigate. They are promptly captured by the megalomaniac Captain Nemo, who skippers a lavish, scientifically advanced submarine.
Widescreen.
Originally released as a motion picture in 1954.
Based on the novel "Vignt Mille lieues sous les mers" by Jules Verne.
Special features: all-new audio commentaries with director Richard Fleischer and classic film historian and author, Rudy Behlmer; original 1954 theatrical radio spots; Peter Lorre's ADR tracks - a glimpse into the process of dialogue replacement before final edit; Captain Nemo's organ music; "The making of 20,000 leagues under the sea" featurette; "Jules Verne & Walt Disney - explorers of the imagination" behind-the-scenes featurette; "The Humboltsquid: real sea monster!"; "Touring the Nautilius"; "Monsters of the deep"; "Nemo's death" script excerpt; "The musical legacy of Paul Smith"; "Lost treasure: the sunset squid sequence"; "Grand Canyonscope"; theatrical trailer; storyboard-to-scene comparision & unused animation.
Director of photography, Franz Planer ; art director, John Meehan ; editor, Elmo Williams ; costume designer, Norman Martien.
Kirk Douglas, James Mason, Paul Lukas, Peter Lorre, Robert J. Wilke, Ted de Corsia, J.M. Kerrigan.
Keywords: Sailors -- Drama; Whaling ships -- Drama; Submarines (Ships) -- Drama; Feature films; Science fiction films; Video recordings for the hearing impaired